2015
DOI: 10.1080/15459624.2014.974808
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Human Viruses on Hands and Risk of Infection in an Office Workplace Using Micro-Activity Data

Abstract: Although the number of illnesses resulting from indirect viral pathogen transmission could be substantial, it is difficult to estimate the relative risks because of the wide variation and uncertainty in human behavior, variable viral concentrations on fomites, and other exposure factors. The purpose of this study was to evaluate the micro-activity approach for assessment of microbial risk by adapting a mathematical model to estimate probability of viral infection from indirect transmission. To evaluate the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 20 publications
(44 reference statements)
3
68
0
Order By: Relevance
“…For hand‐to‐mouth contacts, a distribution used by Beamer et al . (2015) was used . For each surface or orifice contact, there was an equal probability of the right or left hand being used, as it has been shown in behavioural studies that the right and left hands did not have significantly different behaviour sequences .…”
Section: Methodssupporting
confidence: 90%
“…For hand‐to‐mouth contacts, a distribution used by Beamer et al . (2015) was used . For each surface or orifice contact, there was an equal probability of the right or left hand being used, as it has been shown in behavioural studies that the right and left hands did not have significantly different behaviour sequences .…”
Section: Methodssupporting
confidence: 90%
“…31 The phage surrogate data reported here, was recently used to validate this model and assess the efficacy of the HWP at variable phage levels and below the current limit of detection. 20 …”
Section: Discussionmentioning
confidence: 99%
“…1820 The purpose of the current study was to quantitate the effectiveness of a hygiene program, known as the Healthy Workplace Project (HWP), in reducing transmission of viruses in the office environment. Phage tracers were used to monitor changes in virus transmission through the workplace before and after implementation of the HWP.…”
Section: Introductionmentioning
confidence: 99%
“…12 As more care is provided in outpatient facilities, it is increasingly important to understand the potential for disease transmission and study the practices that ensure infection prevention in this setting. Although disinfection interventions have been quantitatively evaluated in hospitals 13,14 and workplaces, 15,16 studies have not been published measuring their effect in health care facilities beyond hospitals, despite evidence of environmental contamination in outpatient care sites. 17,18 Understanding the dynamics of transmission and reservoirs of contamination in an outpatient setting can help inform effective infection control guidelines and practices.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in home and office environments demonstrated that human viruses and virus surrogates spread rapidly throughout a facility and may contaminate more than half of the surfaces within 4 hours. 16,19 Ethanol-based products, particularly those targeting hand hygiene, play a strong role in infection control because of rapid, broad-spectrum efficacy and ease of use. For surface disinfection, however, ethanol-based disinfectants have required high levels of alcohol (50%) for antimicrobial efficacy, which led to concerns with fast dry times and material compatibility.…”
Section: Introductionmentioning
confidence: 99%